Exploration of the Iziko South African Museum's collection and description of new species of Spaghetti worms (Annelida, Terebelliformia), part one - Lavesque, Nicolas; Hutchings, Pat (Zootaxa, 2025)
In this study, we describe four new species of Spaghetti worms (Annelida: Terebellidae and Trichobranchidae) from South Africa, based on specimens stored since several decades in the Iziko South African Museum in Cape Town. The first one, Eupolymnia scholastica sp. nov. from Western Cape, is characterised by the presence of small lateral lobes present on segments II-IV, the presence of branchiae with short basal stems and well-developed branches and uncini with a main fang surmounted by crests with two rows of secondary teeth and upper crest of several small denticles. The three other species belong to Terebellides genus. The first one, T. marionensis sp. nov. from Marion Island (sub-Antarctic Indian Ocean), has a glandular lateral region on segment V, branchial lamellae without papillar projections and the presence of branchial lobes almost free from each other, terminating with short pointed tips. The second one, T. simonae sp. nov. from Western Cape, is characterised by the presence of a large glandular oval lateral region on segment V, the presence of papillar projections on margins only on the most anterior branchial lamellae and the presence of free branchial lobes terminating with filaments. Finally, T. talboti sp. nov. also described from Western Cape, has no glandular lateral region on segment V but has papillar projections on the margins of the branchial lamellae and the branchial lobes which are fused for approximately 1/2 of length terminating with pointed projections.